(untitled) (Research, Society and Development, 2021)
Studies aimed at the field of Hospital Pharmacy, especially those aimed at evaluating its services, are considered to be themes that are little explored in the scientific community. The aim of this study was to analyze the importance of evaluating the quality of Hospital Pharmacy services through a strategic basic purpose survey, with a descriptive and exploratory objective, with a qualitative approach, having as a research instrument the narrative literature review, delimited by scientific researches by authors in the field of hospital pharmacy. Works were analyzed in a time frame between 2007 and 2020, in which it was possible to identify, in these bibliographical studies, the evaluations of how this process allows the identification of errors, the indication of indicators, and consequently how it allows the improvement of them and their improvement to the minimum standards indicated, demonstrating the importance of constantly evaluating the provision of these services. This bibliographic analysis made it possible to establish the effectiveness of the evaluation of the activities provided to modify the provision of hospital pharmaceutical services and, consequently, increase the quality of health services, expanding the scientific production on this topic in the thematic area of hospital pharmacy.